Perceptions of the Self Versus One’s Own Social Group: (Mis)conceptions of Older Women’s Interest in and Competence With Technology - Gales, Alina; Hubner, Sylvia V. (Frontiers in Psychology, 2020)
Our analysis investigates how gender, age, and technology stereotypes relate to one another and how this relationship reinforces or questions stereotypes. Based on intersectionality, stereotyping and sense-making literature, our study explores how older women perceive their own interest in and competence with technology and that of their peers. We conducted qualitative in-depth interviews with women between 65 and 75 years of age in Germany. Our findings indicate that their evaluations of others are age and gender stereotyped. When explaining their own interest in technology, they refer to their individual preferences, and for explaining their own competence of technology, they refer to social categories. Plus, assumptions of technology usage seem to be gendered. On the basis of our findings, we discuss the need for taking social categories into account when evaluating inclusiveness with new technologies.